Taking action for social change - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
Research at the SMU Lien Centre for Social Innovation is helping to better understand and respond to the needs of vulnerable communities in Singapore. See the papers: Elderly population in Singapore: Understanding social, physical and financial needs Single-parent families in Singapore: Understanding the challenges of finances, housing and time poverty People with physical disabilities in Singapore: Understanding disabling factors in caregiving, education, employment and finances A handbook on inequality, poverty and unmet social needs in Singapore